ANALYSIS OF DEFECTS IN BULK SEMICONDUCTORS USING ELECTRON CHANNELING CONTRAST IMAGING - Czernuszka, J; Long, N; Hirsch, P (Publ by Inst of Physics Publ Ltd, 1991)
Electron channelling contrast imaging (ECCI) is a SEM based technique for imaging and characterising the Burgers vectors of dislocations in bulk samples. Thus, thin foil relaxation effects do not occur and specimen preparation is relatively straightforward. In this paper we present preliminary results of a study on dislocations and precipitates in bulk samples of deformed Si. It has been shown that increasing signal acquisition times improves the signal to noise ratio and the depth to which dislocations can be imaged. The precipitates have been imaged using strain contrast and atomic number contrast.